(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Sustainable tourism has become an important issue in the hospitality industry, especially in tourist destinations such as Bali. Alila Villas Uluwatu, as a five-star hotel located in Pecatu Village, applies the concept of sustainability through environmentally friendly practices in various aspects of its operations, including at Cire Restaurant. This study aims to analyze the implementation of Green Practice at Cire Restaurant and its impacts on the environment, society, and economy in Pecatu Village. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews with restaurant management and staff, and analysis of related documents. The results of the study show that the implementation of Green Practice at Cire Restaurant includes three main aspects: Green Action, Green Food, and Green Donation. The impact of the implementation of Green Practice is quite significant. Thus, the sustainability practices implemented at Cire Restaurant Alila Villas Uluwatu not only provide benefits for the hospitality business itself but also have a positive impact on the environment and surrounding communities